(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Idiopathic scoliosis of varying degrees and severity was studied (216 children) in terms of the age of the initial manifestation of spinal deformity. It has been established that the first clinical signs of scoliotic deformity appear at the age of no more than 10 years. those. before the beginning of the period of physiological maturation of the organism. Analysis of the data obtained makes it possible to determine the proportions of various variants of natural development and predict the prospects for the development of pathology in patients with idiopathic scoliosis.